Congenital Cytomegalovirus infection - current reports on prevention, diagnosis and effective therapy - Wacławska, Monika; Wacławska, Marcelina; Wieteska, Małgorzata; Maj, Dominik (Journal of Education, Health and Sport, 2022)
Congenital CMV-cCMV- infection is the most common congenital viral infection in the world, especially in developing countries. It is a serious problem because it can contribute to the development of severe neurodevelopmental disorders and is also the main cause of sensorineural hearing loss. A high risk of adverse effects on the fetus occurs with CMV infection in early pregnancy, but infection can be transmitted from mother to fetus also in cases of secondary infections. Despite the high prevalence of up to 2% of all births, screening for CMV has not yet been established and diagnostic and therapeutic strategies have not been standardized. The aim of this article is to review the current reports on the early detection of congenital CMV, as well as effective methods of its prevention and the best treatment. Unfortunately, the literature review shows that there are no preventive measures other than proper hygiene during pregnancy. However, many clinical trials are currently underway to develop a CMV effective vaccine. Currently, the infection can be detected already at the stage of fetal life using PCR tests detecting the genetic material of the virus in the amniotic fluid. However, the treatment of already diagnosed congenital CMV is based on antiviral therapy for a period of 12 months, but only in symptomatic infants due to side effects such as neutropenia. Currently, the effectiveness of such treatment reduces the percentage of children with hearing loss and neurological disorders. Pregnant mothers should be educated on how to prevent infections, and doctors' task is to update data on the latest diagnostic and therapeutic recommendations.